Integrating antibody drug conjugates in the management of gynecologic cancers. Issue 3 (6th March 2023) - Chelariu-Raicu, Anca; Mahner, Sven; Moore, Kathleen Nadine; Lorusso, Domenica; Coleman, Robert L
Abstract : The clinical development of antibody drug conjugates (ADCs) in ovarian cancer began in 2008 with farletuzumab, a humanized monoclonal antibody, and vintafolide, an antigen drug conjugate, both targeting alpha folate receptor. Over the years, this novel class of drugs expanded to agents with a more sophisticated design and structure, targeting tissue factor (TF) in cervical cancer or human epidermal growth factor receptor 2 (HER2) in endometrial cancer. Despite the impressive number of patients included in clinical trials investigating different ADCs across gynecological cancers, it was only recently that the Food and Drug Administration (FDA) granted accelerated approvals to the first ADCs in gynecologic cancer. In September 2021, the FDA approved tisotumab vedotin (TV) in recurrent or metastatic cervical cancer with disease progression on or after chemotherapy. This was followed in November 2022, by the approval of mirvetuximab soravtansine (MIRV) for adult patients with folate receptor alpha (FRα) positive, platinum-resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer, who have received one to three prior systemic treatment regimens. Currently, the field of ADCs is rapidly expanding and more than 20 ADC formulations are in clinical trials for the treatment of ovarian, cervical and endometrial tumors. This review summarizes key evidence supporting their use and therapeutic indications, including results from late-stage development trials investigating MIRV in ovarian cancer and TV in cervical cancer. We also outline new concepts in the field of ADCs, including promising targets such as NaPi2 and novel drug delivery platforms such as dolaflexin with a scaffold-linker. Finally, we briefly present challenges in the clinical management of ADC toxicities and the emerging role of ADC combination therapies, including chemotherapy, anti-angiogenic and immunotherapeutic agents.